Money matters…but so do people: Children's views and experiences of living in a 'disadvantaged' community. (February 2019) - Bessell, Sharon
Abstract: In recent years there has been increased interest among scholars and policy makers in the ways in which communities support or fail children. There has also been interest, particularly among policy makers and practitioners, in how disadvantaged communities can be strengthened to better support children. This paper draws on qualitative research, conducted with 108 children aged between eight and twelve years, in six communities across eastern Australia. Using a rights-based methodology and drawing on participatory methods, the research sought to understand, from the perspective of children, what makes a strong and supportive community. The paper presents two key themes that arose from the research. First, it explores the ways in which financial disadvantage and inadequate public infrastructure and services diminish children's experience of community. Second, it highlights the centrality of inter-personal and inter-generational relations to children's perceptions of whether their community is strong and supportive. It argues that while family finances and public services are central in shaping children's experience of community, strong and supportive relationships are of equal importance.